Effect of magnesium sulfate with propofol induction of anesthesia on succinylcholine-induced fasciculations and myalgia - Mahendra Kumar; Nalin Talwar; Ritu Goyal; Usha Shukla; A K Sethi (Wolters Kluwer Medknow Publications, 2012)
Background: Magnesium sulfate and propofol have been found to be effective against succinylcholine-induced fasciculations and myalgia, respectively, in separate studies. A prospective randomized double blind controlled study was designed to assess the effect of a combination of magnesium sulfate with propofol for induction of anesthesia on succinylcholine-induced fasciculations and myalgia. Materials and Methods: Randomly selected 60 adult patients scheduled for elective surgery under general anesthesia were allocated to one of the two equal groups by draw of lots. The patients of MG Group were pretreated with magnesium sulfate 40 mg/kg body weight in 10 ml volume, while patients of NS group were given isotonic saline 0.9% in the same volume (10 ml) intravenously slowly over a period of 10 min. Anesthesia was induced with fentanyl 1.5 mcg/kg and propofol 2 mg/kg, followed by administration of succinylcholine 2 mg/kg intravenously. Muscle fasciculations were observed and graded as nil, mild, moderate, or severe. Postoperative myalgia was assessed after 24 h of surgery and graded as nil, mild, moderate, or severe. Observations were made in double blind manner. Results: Demographic data of both groups were comparable (P> 0.05). Muscle fasciculations occurred in 50% patients of MG group versus in 100% patients of NS group with a significant difference (P< 0.001). After 24 h of surgery, no patient of MG group and 30% patients of NS group had myalgia with a significant difference (P< 0.002). Conclusion: Magnesium sulfate 40 mg/kg intravenously may be used with propofol for induction of anesthesia to control succinylcholine-induced fasciculations and myalgia.